1995
DOI: 10.1021/ja00135a036
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nitrogen Ring-Expansion Process Facilitated by in Situ Hemiketal Formation. An Asymmetric Schmidt Reaction

Abstract: We recently reported an intramolecular version of the Schmidt reaction' in which hydrazoic acid was replaced by an alkyl azide connected to the reactive ketone.2 This is an unusual example of intramolecularity because the analogous H+-promoted intermolecular reaction does not succeed at alL3 Given the potential utility of a general method for the intermolecular insertion of an N-alkyl group adjacent to a ketone, other conditions to effect the direct reaction of ketones with alkyl azides were examined. Of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…6 Although previously disclosed studies with acetone and 1b showed solely amide product in 86% yield when NaHCO 3 was used, 2 we have had difficulty in repeating this result. Current work to elucidate the effect of ketone and azide structures on the distribution of acyclic products is underway.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…6 Although previously disclosed studies with acetone and 1b showed solely amide product in 86% yield when NaHCO 3 was used, 2 we have had difficulty in repeating this result. Current work to elucidate the effect of ketone and azide structures on the distribution of acyclic products is underway.…”
Section: Methodsmentioning
confidence: 83%
“…6 Only amide formation was observed in our previous studies with four-to six-membered ring ketones, using either base in the work-up. [2][3][4] The difference in transannular strain associated with the lactams (standard rings, 5-7 members) vs. lactones (medium rings, 8-11 members) formed in these cases most likely accounts for the absence of lactone production. In contrast, both products from the ring expansion of cycloheptanone contain medium-to-large rings and therefore, ring strain is likely to play a less dominant role in product selection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction represents an alternative to Schmidt reaction using hydroxyalkyl azides. [22][23][24][25][26][27][28] Studies of halogen-induced oxidative rearrangements of N,O-ketals were performed using 1a as a test substrate. Compound 1a was readily prepared by the condensation of cyclobutanone with a commercially available amino alcohol, 2-amino-3-phenylpropan-1-ol.…”
mentioning
confidence: 99%
“…The iminium ether intermediate ii has ambident electrophilicity, and the C2 and C4 positions of the oxazoline ring can react with nucleophiles. [22][23][24][25][26][27][28][30][31][32][33] Methyl ether 3a′ is not produced, and therefore nucleophilic attack by MeOH on intermediate ii selectively occurs at the C2 position rather than the C4 position of the oxazoline ring, to give a possible intermediate iii, which affords alcohol 3a on aqueous work-up.…”
mentioning
confidence: 99%